Diversity Analysis of Distributed Space-Time Codes in Relay Networks with Multiple Transmit/Receive Antennas. (3rd April 2008) - Jing Jing, Yindi Yindi; Hassibi Hassibi, Babak Babak
Abstract : The idea of space-time coding devised for multiple-antenna systems is applied to the problem of communication over a wireless relay network, a strategy called distributed space-time coding, to achieve the cooperative diversity provided by antennas of the relay nodes. In this paper, we extend the idea of distributed space-time coding to wireless relay networks with multiple-antenna nodes and fading channels. We show that for a wireless relay network withM antennas at the transmit node, N antennas at the receive node, and a total ofℛ antennas at all the relay nodes, provided that the coherence interval is long enough, the high SNR pairwise error probability ( PEP ) behaves as( 1 / P ) min { M, N } ℛ ifM ≠ N and( log 1 / M P / P ) ℳ ℛ ifM = N, whereP is the total power consumed by the network. Therefore, for the case ofM ≠ N, distributed space-time coding achieves the maximal diversity. For the case ofM = N, the penalty is a factor oflog 1 / M P which, compared toP, becomes negligible whenP is very high.